PENGARUH BABYSPA TERHADAP PERKEMBANGAN MOTORIK KASAR DAN HALUS PADA BAYI USIA 6-12 BULAN DI SUNRISE BABY SPA KOTA MALANG - Zhafirah, Muti’ah Jihan; Keswara, Nila Widya; Wijayanti, Tut Rayani Aksohini (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
This study aims to investigate the effect of baby spa therapy on gross and fine motor development in babies aged 6–12 months at Sunrise Baby Spa, Malang City. We used a quasi-research method with a one-group pretest-posttest design, involving 20 babies who underwent baby spa therapy. We collected data using gross and fine motor development questionnaires, and processed the results using univariate, bivariate, and Wilcoxon statistical tests. The results showed a significant increase in gross motor development after baby spa therapy, with 80% of respondents achieving development in accordance with the expected stages after therapy. The Wilcoxon statistical test shows a P value of 0.000, confirming that there is a significant difference between the pretest and posttest conditions. Likewise, with fine motor development, the results showed a significant improvement after baby spa therapy, with 50% of respondents achieving development in accordance with the expected stages after therapy. The Wilcoxon statistical test shows a P value of 0.000, confirming that there is a significant difference between the pretest and posttest conditions in fine motor development. The conclusion of this study is that baby spa therapy positively influences gross and fine motor development in babies aged 6–12 months, showing potential as an effective method for improving motor skills in babies.